Celebrating Culture - Fang, Wei-Ta. author. (orcid)0000-0002-4460-0652 Link aut Link
XXX, 454 p. 147 illus., 130 illus. in color.
Keywords: This book provides a comprehensive exploration of festival-making activities, their cultural significance, and their impact on tourism and community identity. It delves into the evolution of festivals, from traditional folk celebrations to modern, tourism-driven events, offering insights into how these festivities shape cultural heritage, economic development, and social cohesion in an increasingly globalized world. A distinguishing feature of this book is its use of integrated references, illustrations, diagrams, and case studies, making complex theories more accessible and engaging. Richly illustrated with vibrant images of festivals from around the world, it not only serves as an academic resource but also as a visual celebration of diverse cultural traditions. This book bridges theoretical concepts with practical implementation, making it a valuable resource for researchers, postgraduate students, and professionals in various fields, including tourism management, anthropology, cultural and creative industries, event planning, and folklore studies. The book is also essential for policymakers, cultural heritage advocates, and business professionals who seek to leverage festivals as a means of economic and cultural development.